Palladium-modified functionalized cyclodextrin as an efficient and recyclable catalyst for reduction of nitroarenes. Issue 10 (20th January 2016) - Guo, Yafei; Li, Jiuling; Zhao, Fen; Lan, Guineng; Li, Liang; Liu, Yuqi; Si, Yunsen; Jiang, Yubo; Yang, Bo; Yang, Rui
Abstract : A kind of palladium-modified functionalized cyclodextrin catalytic system was synthesized and characterized. It showed high activity in the reduction of nitroarenes with the absence of sodium borohydride in water at room temperature. Abstract : A palladium-modified functionalized cyclodextrin (DACH-Pd-β-CD) catalytic system was synthesized and characterised. It showed high catalytic performance in the reduction of different nitroarenes to the corresponding anilines with the presence of sodium borohydride in water at room temperature. The yields of the desired products are up to 99%. Furthermore, the catalyst can be easily separated and still could maintain high catalytic activity after five cycles and no leaching of Pd into solution occurred.